2014
DOI: 10.17755/esosder.18509
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Foreign Language Teaching Model for Undergraduate Programs in Tourism

Abstract: Referring to the fact that the tourism sector offers a lot of job opportunities tourism undergraduate programs have an important place in the tourism education system in Turkey.Due to the importance of foreign language (FL) skills in the tourism sector, it is necessary to revise foreign language teaching models of these programs. The purpose of the study is to determine the perceptions, expectations and suggestions of students and faculty members regarding the foreign language teaching models applied in underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In addition, the fact that creative writing activities are not given much place in the classrooms can be seen as a reason for this situation. According to Temizkan (2010), the element of extraordinaryness should be included in creative writings. In addition, it is possible to say that the codes of producing solutions in the face of problems (n=11), curiosity (n=8), adventure (n=6) and mystery (n=4) are very few in the articles.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In addition, the fact that creative writing activities are not given much place in the classrooms can be seen as a reason for this situation. According to Temizkan (2010), the element of extraordinaryness should be included in creative writings. In addition, it is possible to say that the codes of producing solutions in the face of problems (n=11), curiosity (n=8), adventure (n=6) and mystery (n=4) are very few in the articles.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The findings obtained in the studies, in which written expression skill levels of students in different grades of secondary schools are examined Temizkan, 2003;Bayram and Erdemir, 2006;Arıcı and Ungan, 2008) showed that primary school students could not reach the level targeted in the programs in terms of written expression skills. Yılmaz (2012) stated "it is a fact that primary school students have problems in terms of writing compositions".…”
Section: Discussionmentioning
confidence: 99%
“…Los hallazgos reflejan la relevancia del turismo en el desarrollo social y económico de las regiones, así como la creciente importancia de las lenguas extranjeras, especialmente del inglés, en la provisión de servicios turísticos y su estrecha relación con la vocación de los territorios. Introduction Foreign languages play a fundamental role in exchanges pertaining to the spheres of cultural, social, and economic life; in an international context, where English stands out as the most influential international language worldwide (Chumaña- Suquillo et al, 2017;Temizkan & Temizkan, 2014;Vugman, Casinelli & Lizárraga, 2019), followed by Spanish and Chinese (Chumaña-Suquillo et al, 2017). Such is the case of tourism, an activity of which its use of English especially is essential to the provision of services (Amirbakzadeh & Alroaia, 2020;Chumaña-Suquillo, Llano-Zhinin & Cazar-Costales, 2017;Manyoma-Ledesma & Barrio-Vargas, 2011;Temizkan & Temizkan, 2014).…”
Section: Introductionunclassified
“…Introduction Foreign languages play a fundamental role in exchanges pertaining to the spheres of cultural, social, and economic life; in an international context, where English stands out as the most influential international language worldwide (Chumaña- Suquillo et al, 2017;Temizkan & Temizkan, 2014;Vugman, Casinelli & Lizárraga, 2019), followed by Spanish and Chinese (Chumaña-Suquillo et al, 2017). Such is the case of tourism, an activity of which its use of English especially is essential to the provision of services (Amirbakzadeh & Alroaia, 2020;Chumaña-Suquillo, Llano-Zhinin & Cazar-Costales, 2017;Manyoma-Ledesma & Barrio-Vargas, 2011;Temizkan & Temizkan, 2014). As Amirbakzadeh & Alroaia (2020) point out, a foreign language has a crucial role to play in the management of these services in order to generate understandable communication with visitors that do not speak the native language, and thus creating better international relations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation